Desulfurization Efficiency Preserved in a Heterometallic MOF: Synthesis and Thermodynamically Controlled Phase Transition. Issue 7 (8th February 2019) - Han, Yi; Sinnwell, Michael A.; Teat, Simon J.; Sushko, Maria L.; Bowden, Mark E.; Miller, Quin R. S.; Schaef, Herbert T.; Liu, Lili; Nie, Zimin; Liu, Jun; Thallapally, Praveen K.
Abstract: Efficient removal of heterocyclic organosulfur compounds from fuels can relieve increasingly serious environmental problems (e.g., gas exhaust contaminants triggering the formation of acid rain that can damage fragile ecological systems). Toward this end, novel metal‐organic frameworks (MOFs)‐based sorbent materials are designed and synthesized with distinct hard and soft metal building units, specifically {[Yb6 Cu12 (OH)4 (PyC)12 (H2 O)36 ]·(NO3 )14 · x S} n (QUST‐81) and {[Yb4 O(H2 O)4 Cu8 (OH)8/3 (PyC)8 (HCOO)4 ]·(NO3 )10/3 · x S} n (QUST‐82), where H2 PyC = 4‐Pyrazolecarboxylic acid. Exploiting the hard/soft duality, it is shown that the more stable QUST‐82 can preserve desulfurization efficiency in the presence of competing nitrogen‐containing contaminate. In addition, thermodynamically controlled single‐crystal‐to‐single‐crystal (SC–SC) phase transition is uncovered from QUST‐81 to QUST‐82, and in turn, mechanistic features are probed via X‐ray diffraction, inductively coupled plasma atomic emission spectroscopy, and ab initio molecular dynamics simulations. Abstract : Thermodynamically controlled hetero‐metallic metal‐organic frameworks (MOFs) are able to preserve the desulfurization efficiency in the presence of competing nitrogen contaminate. The preserved adsorption capacity for organosulfur is shown to originate from the dual hard/soft Lewis acid nature in the heterometallic MOF.